Forest Aesthetics as a Basic Idea for Forest Management from the Perspectives of Light Quality, Ecosystems, and Sustainability in Japan - Koike, Tatsunori; Koike, Takayoshi; Ueda, Hirofumi (Studia Historiae Oeconomicae, 2024)
Forest conservation as a living environment is essential for human survival. Attention is focused on Forest Aesthetics created by von H. Salisch at Postel in Poland, who managed economic forests to realize their functional beauty. Although an idea of Salisch introduced to Japan by 1895, lectures on Forest Aesthetics did not continue in universities located in middle latitudes. The main reason is that Forest Aesthetics depends on stand structure, creating sunshine filtering through canopy on the forest floor and the incident light makes the forests look beautiful. Action of light quality also plays an important role in forest beauty. Forest Aesthetics encompasses the ideas of ecosystems, sustainability, and family affection. Although Forest Aesthetics was proposed in 1885, there was no scientific term of “ecosystem” and ecological service that time. Now once again, it is about time to reevaluate the Forest Aesthetics produced in land of Poland.